2021
DOI: 10.1055/a-1503-3875
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Atrial Fibrillation in Older Patients: Does Oral Anticoagulant Therapy Provide a Survival Benefit?—An Insight from the GeroCovid Registry

Abstract: Introduction. Atrial fibrillation (AF), the most frequent arrhythmia of older patients, associates with serious thrombo-embolic complications and high mortality. COVID-19 severely affects aged subjects, determining an important prothrombotic status. Aim of this study was to evaluate mortality-related factors in older AF patients with COVID-19. Methods. Between March and June 2020, we enrolled >=60 years in-hospital COVID-19 patients (N=806) in GeroCovid, a multicenter observational study promoted by the It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“…In GeroCovid, no differences in COVID-19 disease severity at admission were observed by arrhythmia status. However, as mentioned above, AF patients presented a higher degree of functional dependency, with this factor being significantly associated with mortality and further strengthened by the lack of use of oral anticoagulants [ 10 ]. Indeed, some population studies found that the years lived with disability and the disability-adjusted life years are progressively increasing when AF is present, with a trend closely mirroring the prevalence of the arrhythmia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In GeroCovid, no differences in COVID-19 disease severity at admission were observed by arrhythmia status. However, as mentioned above, AF patients presented a higher degree of functional dependency, with this factor being significantly associated with mortality and further strengthened by the lack of use of oral anticoagulants [ 10 ]. Indeed, some population studies found that the years lived with disability and the disability-adjusted life years are progressively increasing when AF is present, with a trend closely mirroring the prevalence of the arrhythmia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of the study, given the distribution of the variable in our population, we categorized patients as without vs. with functional limitations, by grouping levels 1 and 2 (the patient can walk independently or with a cane) and levels 3–7 (the patient can walk using a walker; the patient can move around with a wheelchair; the patient does not move around but he is accompanied outside on the wheelchair; the patient is confined at home, mostly lying on the bed; the patient does not autonomously stand up or get in sitting position) [ 10 ]. According to the World Health Organization (WHO) classification and on patients’ distribution, the baseline severity of COVID-19 was defined as mild with no oxygen support needed, mild with low-flow oxygen support needed, and severe or critical (high-flow oxygen support required, need of non-invasive or invasive mechanical ventilation, or organ support) [ 10 ]. Finally, data on in-hospital mortality were also recorded for all the study participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 The multicenter observational GeroCovid study, presented convincing data on the role of direct oral anticoagulants (DOACs) in reducing the risk of death in COVID-19 older patients. 19 While the beneficial anticoagulation effects of heparin on the thrombotic arm of COVID-19 is easily explicable, intriguing data from Mycroft-West et al suggested that heparin may also prevent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from infecting cells, 20 opening options for repurposing heparin and its derivatives as antiviral agents.…”
Section: Understanding and Managing Covid-19mentioning
confidence: 99%
“…5,14 Most studies are focused on analyzing the risk of thromboembolic events and complications from the COVID-19 infection in patients on anticoagulant treatment once hospitalized. [15][16][17]…”
Section: Eupas Register: Eupas37205mentioning
confidence: 99%